Pengaruh Kompetensi, Iklim Organisasi, Dan Kepuasan Kerja Terhadap Prestasi Kerja Melalui Komitmen Organisasi: The Influence of Competence, Organisational Climate and Job Satisfaction on Work Performance via Organisational Commitment - Kristanty Lidya Tarihoran; Herry Krisnandi (OGZ Research & Publishing, 2026)
Objective : A study to analyse the influence of competence, organisational climate and job satisfaction on work performance, with organisational commitment as an intervening variable, at the Air Police Directorate of KORPOLAIRUD BAHARKAM POLRI. Methodology : A total of 303 personnel were selected as a sample using non-probability sampling techniques. Data was collected using a questionnaire and analysed using Structural Equation Modelling (SEM). Research Results : The findings of the study indicate that competence and job satisfaction influence work performance, whereas organisational climate does not have a direct influence on job satisfaction. With regard to indirect effects, the results show that commitment and job satisfaction influence work performance via organisational commitment, whereas organisational climate does not influence job satisfaction via organisational commitment.